The larvae of European Myrmeleontidae (Neuroptera) - Badano, Davide; Pantaleoni, Roberto Antonio (Zootaxa, 2014)
The larvae of the European Myrmeleontidae are reviewed with the aim to ease their identification, covering 15 genera and 28 species. Diagnostic characters and illustrations are given for each taxon. Larvae of the genera Nemoleon and Macronemurus are described for the first time while Megistopus, Neuroleon and Myrmeleon are revised. The larvae of Dendroleon pantherinus (Fabricius), Macronemurus appendiculatus (Latreille), Megistopus lucasi (Navás), Nemoleon notatus (Rambur), Neuroleon arenarius (Navás), Neuroleon assimilis (Navás), Neuroleon nemausiensis (Borkhausen), Cueta lineosa (Rambur) and Myrmeleon gerlindae (Hölzel) are described or accurately depicted for the first time.